Investigating the compressive strength and strain localization of nanotwinned nickel alloys. (1st February 2021) - Valentino, Gianna M.; Xiang, Sisi; Ma, Luoning; Xie, Kelvin Y.; He, Mo-Rigen; Oliver, Warren C.; Pharr, George M.; Krogstad, Jessica A.; Weihs, Timothy P.; Hemker, Kevin J.
Abstract: Sputter deposited nickel-molybdenum-tungsten (Ni-Mo-W) thin films possess a beneficial suite of properties that stem from the extremely fine growth twins that form during the deposition process. Previously these materials were only characterized in tension, however, in this study in situ micropillar compression and post-mortem microstructural analysis of nanotwinned Ni84 Mo11 W5 micropillars were employed to measure the compressive response and elucidate the attendant deformation mechanisms. The pillars exhibit Hookean behavior to compressive strengths of 3-3.5 GPa and the onset of non-linear plastic flow was manifest by discrete strain bursts and highly localized shear bands. Plastic deformation was concentrated at the top of the pillar, while the bulk of the micropillar was nominally unaffected. Post-mortem investigations indicate that at sufficiently high stresses shear banding is triggered, resulting in intense and highly localized plastic deformation that led to the formation of twin-free nanocrystalline grains within highly deformed shear bands. By contrast, the regions adjacent to the shear bands were unaffected. The absence of detwinning and dislocation glide mechanisms was unexpected and in direct contrast to what has been observed in nanotwinned Cu-Al. Post-mortem observations of the Ni-Mo-W micropillars suggest that the ultrafine twins create a unique form of dislocation starvation and source-limited plasticity. The ultrahigh compressive strength is governed by the triggering of shear bands rather than the activation of dislocation glide. The specialized nature of plasticity in nanotwinned Ni-Mo-W is clear, even though the precise trigger for shear band formation in nanotwinned Ni-Mo-W remains to be identified. Graphical abstract: Image, graphical abstract